Inside Back Cover: Artifact‐Free Quantification and Sequencing of Rare Recombinant Viruses by Using Drop‐Based Microfluidics (ChemBioChem 15/2015). Issue 15 (October 2015) - Tao, Ye; Rotem, Assaf; Zhang, Huidan; Cockrell, Shelley K.; Koehler, Stephan A.; Chang, Connie B.; Ung, Lloyd W.; Cantalupo, Paul G.; Ren, Yukun; Lin, Jeffrey S.; Feldman, Andrew B.; Wobus, Christiane E.; et al.
<x xml:space="preserve">Abstract</x> The inside back cover picture shows a novel drop‐based microfluidics method to detect very rare viral recombinants. Viral recombination has a significant impact on virus evolution and epidemiology; however, a number of challenges prevent its accurate quantification and mechanism analysis, including low frequency, the uncertainty of breakpoints and chimeric artifacts generated during amplification due to the co‐existing different parent viruses. The core advantage of our method originates in compartmentalization of single viral genomes; this fundamentally avoids the generation of chimeras. Furthermore, the high‐throughput isolation of the recombinants by using drop‐based fluorescence sorting allows the screening of ∼107 viral genomes one by one in two hours.